NIAT BERWIRAUSAHA DI KALANGAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS UDAYANA DAN UNIVERSITAS WARMADEWA - Dewi, Ni Putu Leni Ratna; Nurcaya, I Nyoman (E-Jurnal Manajemen, 2017)
Entrepreneurship has an important role in improving the economy of a country, so it is expected that every citizen should have the intention to entrepreneurship. Study aimed to test the intentions of entrepreneurship among students of the faculty of economics and business university and university udayana Warmadewa. The samples used were 110 respondents to the respondents UNUD FEB 54 and FE UNWAR as many as 56 by using a non-probability sampling techniques, particularly purposive sampling. Data collection is done by distributing questionnaires. Analysis technique used is descriptive analysis techniques and different test t-test. Each variables tested have valid and reliable. The results showed that there was a significant difference to the average intention of entrepreneurship among students FEB UNUD and FE UNWAR views of the variable needs for achievement, subjektif norm, and locus of control in which the average value of goodwill entrepreneurship FEB students UNUD higher than students FE UNWAR.
Keywords: need for achievement, subjective norms, and locus of control